Autonomous robotic system-assisted trans-inferior alveolar nerve implantation for patient diagnosed with pemphigoid: a case report - Mucong Li; Huixin Lv; Yidi Zhang; Xiuyu Liu; Kewen Jia; Jiaqian You; Siyu Chen; Yanmin Zhou (BMC Oral Health)
Abstract Background Inadequate bone height and the proximity of the inferior alveolar nerve following vertical resorption of the mandibular alveolar ridge pose great challenges for dental implant surgery. Pemphigoid is a chronic autoimmune disease affecting both the skin and mucous membranes. The presence of autoantibodies and the ongoing inflammatory response significantly impair the skin’s ability to heal in pemphigoid patients, thus necessitating a minimally invasive surgical approach. Therefore, finding accurate and minimally invasive implant solutions to address insufficient bone height in the mandibular posterior region for pemphigoid patients is highly important. Case presentation A 35-year-old female patient with pemphigoid presented with multiple missing posterior mandibular teeth requested dental implants. CBCT examination revealed substantial vertical resorption of the mandible in the right posterior region. Taking into account the patient’s overall health condition, potential surgical trauma, and treatment duration, an autonomous dental implant robot was utilized to perform trans-inferior alveolar nerve implantation. Conclusion Autonomous robotic system-assisted trans-inferior alveolar nerve implantation not only maximized the use of the patient’s existing bone volume and shortened the treatment period but also ensured the precision of implant placement. At the same time, the flap range of the implant surgery was greatly reduced, thereby decreasing the risk of postoperative soft tissue complications for patients with pemphigoid.